The economics of excess: addiction, indulgence, and social policy - Winter, Harold (Stanford Economics and Finance, an imprint of Stanford University Press, 2011)
The economics of addiction -- Smoking can kill you -- Let's drink to your health -- All you can eat -- We know what's best for you -- The new paternalism : final thoughts